2022
DOI: 10.2147/opth.s359710
|View full text |Cite
|
Sign up to set email alerts
|

Pachymetric Assessment After EpiSmart® Epithelium-on Cross-Linking for Keratoconus and Post-Surgical Ectasia

Abstract: Purpose To assess the change in corneal pachymetry after a novel epithelium-on (EpiSmart ® ) corneal crosslinking procedure (CXL). Methods Eyes treated as part of the open-label, non-controlled arm of the study “Collagen Crosslinking with Ultraviolet-A in Asymmetric Corneas” (NCT01097447) were examined at baseline, 3-, 6- and 12-months post-CXL. Thinnest pachymetry readings based on Pentacam (OCULUS GmbH, Wetzlar, Germany) were recorded. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…This confirms a pilot study which also observed no change in minimal thickness with the EpiSmart technique. 32 …”
Section: Discussionmentioning
confidence: 99%
“…This confirms a pilot study which also observed no change in minimal thickness with the EpiSmart technique. 32 …”
Section: Discussionmentioning
confidence: 99%
“…This might be accomplished by enhancing epithelial penetration and reducing riboflavin photodegradation (Rubinfeld et al, 2021). Recently, they have conducted phase 2 trials of EpiSmart ® epi-on in 1606 KCN patients, and substantiated the excellent safety and efficacy profile of their system during 12-month observation (Epstein et al, 2022;Vaidya et al, 2022).…”
Section: Sodium Iodide (Nai)mentioning
confidence: 99%